The "make/break test" as a diagnostic tool in functional weakness. - van der Ploeg, R J (1991)
Strength was measured in four major muscle groups with a hand-held dynamometer. The "make" and "break" technique was used with and without encouragement, and fatiguability was tested in patients with organic weakness and patients with functional weakness. Patients with functional weakness could be distinguished from the other two groups by an increase in strength greater than 20% with the break compared with the make technique. Additionally they tend to show larger increases in strength with encouragement and their "fatiguability" was less.